Strategi Pengembangan Manajemen Diklat dalam Meningkatkan Daya Saing Lembaga Pendidikan - Mubarok, Ramdanil (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The aim of this research is to analyze training management development strategies that can help increase the competitiveness of educational institutions which focuses on the concept of training management development, training management development strategies in increasing the competitiveness of educational institutions, and the challenges. This research uses library research methods. The research results show that the concept of training management development is a systematic approach to planning, organizing, implementing and evaluating training and development programs to improve individual and organizational performance which includes: planning training, organizing training, implementing training, evaluating training and controlling training. Meanwhile, the development strategy is through comprehensive analysis of training needs, flexibility and responsiveness to change, development of quality teaching staff, use of technology in learning, partnerships with industry and communities, as well as ongoing monitoring and evaluation. The challenges are limited resources, rapid environmental changes, diverse needs of staff and employees, limited time and commitment, as well as various other factors that complicate the planning, implementation and evaluation of training programs.